In-plane behavior and seismic performance of differently detailed, multi-story, perforated, partially grouted masonry walls. (15th November 2022) - Medeiros, Klaus A.S.; Palhares, Rodolfo A.; Parsekian, Guilherme A.; Shrive, Nigel G.; Fonseca, Fernando S.
Highlights: Use of experimental tests and a precise finite element model; Assessment of bilinear and trilinear idealizations for the actual wall response; Walls performing as a continuous frame with confined masonry; Differently detailed walls with similar seismic detailing design efficiency; Changes in the axial load impact the wall strength, ductility, and degradation. Abstract: Partially grouted (PG) masonry structures are widely used in many regions worldwide, especially those regions with low and mid-intensity wind and/or seismic actions. Depending on the design code, the grouted/reinforced cells should be uniformly distributed along a shear wall rather than concentrated. Thus, this study focused on PG shear walls with grout and reinforcement placed at the ends aiming to evaluate their in-plane behavior and seismic performance. Also, the walls examined were three-story and perforated. Finite element models validated against previous experimental tests were used to perform the study. Besides two traditional bilinear idealizations for the actual wall response, a trilinear approach is presented with deduced equations for the seismic performance factors (SPFs). Results demonstrated that the reinforced masonry beam over the openings effectively coupled the wall piers yielding a frame-type action. Also, it appears that the walls performed as a continuous frame, with the grouted parts acting like columns and the ungrouted parts acting like confined masonry. The loss of ductility evidenced in the backbone curves and the decrease of the SPFs confirmed that a high vertical pre-compression led the walls to a brittle response while also increasing the lateral load capacity. Concentrating the grouting and reinforcement at the wall pier ends showed a similar detailing design efficiency compared to distributing them along the wall piers. The stiffness degradation was more intense when the walls were subjected to a lower pre-compression level. Furthermore, the stiffness degradation curves were best fitted with power and logarithmic functions for walls with the lower and higher axial load, respectively.